Cationic oxidized microporous rice starch: Preparation, characterization, and properties - Tang, Hong‐bo; Lv, Xiao‐li; Li, Yan‐ping; Li, Qian; Liu, Xiao‐jun (Journal of food science, 2020)
The combination of enzymolysis of compound enzyme, oxidation of sodium hypochlorite, and cationic etherification of 3‐chloro‐2‐hydroxypropyl trimethyl ammonium chloride (CHPTMA) was selected for the functionalization of rice starch (RS) to better raise the performances. The results showed that the oxidation and etherification could improve the acid and alkali resistance of RS, and enhanced its thermal stability. The crystalline structure of RS was an A‐type, the enzymolysis, oxidation, and etherification did not change the structural type, while the crystallinity degree of RS derivatives was all reduced. The enzymolysis, oxidation, and etherification altered the pasting properties of RS, and could effectively decrease the setback and breakdown of RS. The oxidation of sodium hypochlorite not only damaged RS particles containing no micropores, but also destroyed the particles containing the micropores. The enzymolysis and oxidation more seriously destroyed the crystalline region than cationic etherification. The oxidation could increase the enthalpy change of RS, whereas the enzymolysis and etherification decreased its enthalpy change. In addition, the enzymolysis and oxidation could lead to the evident increase in average size of RS. The cationic etherification was able to improve the adsorption of Cu2+ on RS, whereas the low oxidation could only slightly ameliorate the adsorption of Cu2+. Practical Application Cationic oxidized microporous rice starch as an adsorbent, slow‐release agent, and flocculant will be well used in food, medicine, pesticide, papermaking, waste water treatment, and so on owing to its abundant micropores, anionic groups, and cationic groups as well as small particle size and narrow size range.